Implementasi Larangan Bagi Kepala Desa atas Penyalahgunaan Dana Desa di Kabupaten Pelalawan - Wan Taufik Hidayat; Ardiansah Ardiansah; Sudi Fahmi (Universitas Medan Area, 2022)
The village government as the lowest power body has the original authority to regulate its own household also has the authority and power as a gradual delegation from the government above it, namely the regional government and the central government. The purpose of this study was to analyze the implementation of the prohibition for the village head on misuse of village funds in Pelalawan district based on Law Number 6 of 2014 concerning Villages, analyze the obstacles to its implementation in the field and analyze the efforts made to overcome obstacles in its implementation in the field. The research method is a sociological legal research, the approach used in addition to the legislation approach is a case approach by analyzing cases of Misuse of Village Funds in Pelalawan Regency. The results of this study are that the implementation of the prohibition so that the village head is not corrupt, does not misuse the village fund budget through outreach activities, coordination meetings, technical guidance, binwas and monev both carried out by district and sub-district supervisory officers and facilitation carried out by village assistants, but in almost all villages none of the making templates or banners/billboards calling for the prohibition of such corrupt practices, as well as the lack of community participation in the development process from planning, implementation, supervision to accountability, which should prevent fraudulent acts by village officials.